2020
DOI: 10.1177/1591019919900825
|View full text |Cite
|
Sign up to set email alerts
|

Isolated superior striate vein thrombosis in adults

Abstract: Background Isolated cerebral deep medullary vein thrombosis has been described in the setting of hemorrhagic periventricular white matter lesions in preterm and full-term neonates, but to the best of our knowledge, has never been reported in adults. We present two cases of isolated thrombosis of the superior striate vein occurring in adults that could be analogous to deep medullary vein thrombosis in that they involve deep cerebral veins only without thrombosis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…The CT and MRI findings suggested that the CMBs resulted from no other pathologies; for example, vessels, mineralisation, haemorrhagic infarction, partial volume artifacts, or cavernous angiomas. Isolated superior striate vein thrombosis may cause a thrombotic lesion in the superior portion of the lentiform nucleus and the internal capsule; 6 however, no thrombosed vein or clearly demarcated lesions supported lacunar infarcts in our cases. There was no MRI study before the onset of the infarction in our cases; however, the CMBs were surrounded by an oedema, and the oedema faded out over time, suggesting the CMBs occurred at the same time as or shortly before the onset of the lacunar strokes.…”
Section: Discussioncontrasting
confidence: 68%
“…The CT and MRI findings suggested that the CMBs resulted from no other pathologies; for example, vessels, mineralisation, haemorrhagic infarction, partial volume artifacts, or cavernous angiomas. Isolated superior striate vein thrombosis may cause a thrombotic lesion in the superior portion of the lentiform nucleus and the internal capsule; 6 however, no thrombosed vein or clearly demarcated lesions supported lacunar infarcts in our cases. There was no MRI study before the onset of the infarction in our cases; however, the CMBs were surrounded by an oedema, and the oedema faded out over time, suggesting the CMBs occurred at the same time as or shortly before the onset of the lacunar strokes.…”
Section: Discussioncontrasting
confidence: 68%
“…Twenty-eight records were excluded because they were duplicates. Three additional records were excluded: 1 study included only adults [19], and 2 studies reported outcomes different from those of interest [20, 21]. A total of 14 full-text articles were assessed for eligibility.…”
Section: Resultsmentioning
confidence: 99%
“…Vascular territories between superior striatal veins and deep medullary veins might not be sharply demarcated. Venous ischemic lesion reported by Dr Bianca Mazini et al 1 may include not only venous thrombosis of superior striatal veins but that of deep medullary veins as well. Good prognosis of the two reported patients could be explained by good collateral to inferior striatal veins and/or superficial medullary veins draining to deep and superficial MCVs, respectively.…”
Section: Alternative Routes In High-flow Arteriovenous Shuntsmentioning
confidence: 89%